The Legal Framework of Corporate Governance in Joint-Stock Companies - Hatem Faaeq Mahdi (Indonesian Journal of Law and Economics Review, 2026)
General Background: Corporate governance emerged as a response to recurring financial and managerial crises affecting companies and capital markets worldwide. Specific Background: In joint-stock companies, governance functions as a legal and economic framework regulating relationships among shareholders, boards, management, and stakeholders to ensure transparency and accountability. Knowledge Gap: Despite its growing relevance, the legal and economic dimensions of corporate governance remain insufficiently integrated in existing analyses. Aims: This study examines the legal framework and economic significance of corporate governance in joint-stock companies. Results: Governance enhances stability, investor confidence, and institutional performance. Novelty: The study synthesizes legal and economic perspectives within a unified framework. Implications: Findings support governance adoption to strengthen corporate sustainability and market confidence.Keywords : Corporate Governance, Joint-Stock Companies, Shareholder Rights, Financial Transparency, Economic DevelopmentHighlight : Governance rules enhance transparency, fairness, and protection of shareholder rights, supporting institutional stability and continuity. Weak oversight and accounting practices cause crises, while governance mechanisms reduce corruption and mismanagement risks. Effective implementation strengthens investor confidence, market value, and economic growth across developing and emerging economies.